Lactobacillus species As a Cause of Urinary Tract Infection (Journal of Dhaka Medical College, 2020)
Lactobacillus is a genus of Gram-positive, facultative anaerobic or microaerophilic, rod-shaped, non-spore-forming bacteria.1 In human, they constitute a significant component of microbial flora at a number of body sites, such as the digestive system, urinary system, and genital system. Lactobacillus species are normally a major part of the vaginal microbial flora.2,3,4 As a normal bacterial flora of the vagina the organisms are typically considered contaminants when cultured from urine specimens of female patients. Here we describe the case of a female patient with chronic pyuria and urinary tract symptoms in which Lactobacillus spp. was determined to be the causative microorganism. After proper treatment the patient gets well soon.J Dhaka Medical College, Vol. 27, No.2, October, 2018, Page 215-217